Zoe the beach dragon - Mara, Maddy (Mara, Maddy. Dragon girls, 2023)
"Grace, Zoe, and Sofia are traveling back to the Magic Forest for another adventure as Sea Dragons. The girls must work together and face their fears in order to save a missing turtle leader. Zoe will have to put her surfing skills to work and take the daring lead on this quest. If she doesn't succeed, the Fire Queen will be one step closer to destroying the natural balance of the Magic Forest's seas!"--